Ecosystem Approach To Flood Disaster Risk Reduction - Kamble, RK; Walia, Abhinav; Thakare, MG (International Journal of Environment, 2013)
India is one of the ten worst disaster prone countries of the world. The country is prone to disasters due to number of factors; both natural and anthropogenic, including adverse geo-climatic conditions, topographical features, environmental degradation, population growth, urbanisation, industrlisation, non-scientific development practices etc. The factors either in original or by accelerating the intensity and frequency of disasters are responsible for heavy toll of human lives and disrupting the life support systems in the country. India has 40 million hectares of the flood-prone area, on an average, flood affect an area of around 7.5 million hectares per year. Knowledge of environmental systems and processes are key factors in the management of disasters, particularly the hydro-metrological ones. Management of flood risk and disaster is a multi-dimensional affair that calls for interdisciplinary approach. Ecosystem based disaster risk reduction builds on ecosystem management principles, strategies and tools in order to maximise ecosystem services for risk reduction. This perspective takes into account the integration of social and ecological systems, placing people at the centre of decision making. The present paper has been attempted to demonstrate how ecosystem-based approach can help in flood disaster risk reduction. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 70-82 DOI: http://dx.doi.org/10.3126/ije.v2i1.9209